Salīm kī ḥayāt, inshāʼ pardāzī aur shāʻirī par ek tanqīdī naẓar - Amīr Aurangābādī, Muḥammad (SAMP early 20th-century Indian books project ;, 1947)
Life and works of Vaḥīduddīn Salīm, d. 1928, Urdu poet.